2019
DOI: 10.1038/s41598-019-54009-0
|View full text |Cite
|
Sign up to set email alerts
|

Functional annotation of serine hydrolases in the asexual erythrocytic stage of Plasmodium falciparum

Abstract: Enzymes of the serine hydrolase superfamily are ubiquitous, highly versatile catalysts that mediate a wide variety of metabolic reactions in eukaryotic cells, while also being amenable to selective inhibition. We have employed a fluorophosphonate-based affinity capture probe and mass spectrometry to explore the expression profile and metabolic roles of the 56-member P. falciparum serine hydrolase superfamily in the asexual erythrocytic stage of P. falciparum. This approach provided a detailed census of active … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…Although direct fatty acid import and de novo synthesis of lipids may be possible, our comparative review revealed the presence of an essential P. falciparum exported lipase (PF3D7_1001600; Table S1), hinting that lipid import and its catabolism inside the host RBC before import into the parasite may be important for intraerythrocytic growth (Figure 1C). PF3D7_1001600 has recently been shown to exhibit lipolytic activity in vitro and thus is likely to be functional [66,67]. Membrane biogenesis is also potentially mediated, at least partially, by essential exported proteins.…”
Section: Lipid Homeostasismentioning
confidence: 99%
“…Although direct fatty acid import and de novo synthesis of lipids may be possible, our comparative review revealed the presence of an essential P. falciparum exported lipase (PF3D7_1001600; Table S1), hinting that lipid import and its catabolism inside the host RBC before import into the parasite may be important for intraerythrocytic growth (Figure 1C). PF3D7_1001600 has recently been shown to exhibit lipolytic activity in vitro and thus is likely to be functional [66,67]. Membrane biogenesis is also potentially mediated, at least partially, by essential exported proteins.…”
Section: Lipid Homeostasismentioning
confidence: 99%
“…PfPARE belongs to a plasmodial subfamily of α/β hydrolases, which are enzymes with very diverse specificities . Although its physiological substrates remain unknown, current evidence suggests that PfPARE plays a role in compound detoxification, as illustrated by the diversity of reported antiplasmodial compounds that have induced PfPARE mutations such as pepstatin esters, MMV011438, AN13762, and now a subset of lindenane sesquiterpenoid dimers. , Ester prodrugs are commonly used to mask polar functionalities to improve pharmacological properties and alleviate unwanted side effects by taking advantage of the ubiquity of esterases within pathogenic targets . However, resistance mediated by PfPARE inactivation has developed readily in vitro , highlighting the importance of identifying compounds that are susceptible to PfPARE activity early during drug discovery.…”
Section: Resultsmentioning
confidence: 99%
“…FP probes have been extensively used to study human hydrolases and a couple of examples for malarial serine hydrolases have also been described. [11,29] Elahi et al [30] used FP probes (Figure 4C) to profile the activity of serine hydrolases in the asexual erythrocytic stage of P. falciparum. A combination of gel-and mass spectrometrybased ABPP using a FP-desthiobiotin ABP identified 26 enriched P. falciparum proteins in schizont-stage parasites, of which 21 were serine hydrolase superfamily homologs.…”
Section: Serine Hydrolasesmentioning
confidence: 99%
“…Elahi et al [30] . used FP probes (Figure 4C) to profile the activity of serine hydrolases in the asexual erythrocytic stage of P. falciparum .…”
Section: Dissecting the Roles Of Specific Enzymes And Proteins In P F...mentioning
confidence: 99%